Effects of dredged sediment dumping on trace metals concentrations and macro benthic assemblage at the continental shelf adjacent to a tropical urbanized estuary. (1st October 2020) - Fonseca, E.M.; Fernandes, J.R.; Lima, L.S.; Delgado, J.; Correa, T.R.; Costa, P.M.S.; Baptista Neto, J.A.; Aguiar, V.M.C.
Abstract: This study assesses trace metals and macro benthic fauna in a dumping area for dredged material in the continental shelf of Guanabara Bay (Rio de Janeiro), southeast Brazil. Sampling of the study area was made after the last dredging of Rio de Janeiro, in 2017, removing 2.9 × 10 6  m 3 of sediments that were disposed at a recurrent dumping site. The trace metals Cu, Zn, Pb, Cr and Ni exhibited a pattern of increasing concentrations towards the disposal site. Geoaccumulation index (NIgeo ) and pollution load index (PLI) classified the dumping area as extremely polluted. The benthic macrofauna was composed by Nemertinea, Nematoda, Sipuncula, Annelida-Polychaeta, Mollusca, Crustacea, Brachiopoda and Echinodermata groups. The central station at the dumping site presented a single taxon Corbula patagonica . The benthic diversity decreased towards the disposal site, as observed by richness and diversity indexes that were markedly different among stations. Results presented preliminary data of trace metals in the dumping area revealing severe pollution in the continental shelf of Guanabara bay. Dumping of dredged material seems to negatively affect the macrobenthic community in the study area since richness and diversity increase with distance from the central spot. Highlights: Dumping area for dredged sediments was sampled for trace metals and macrobenthos. Geoaccumulation and Pollution Load indexes revealed contamination by trace metals. Only one specie was found in the central dumping spot, Corbula patagonica. Trace metal concentrations increased towards central dumping spot. Richness and diversity of biota increased with distance from the central dumping spot.